2002
DOI: 10.1155/2002/545612
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow‐up of Ventilated Patients with Thoracic Restriction and Neuromuscular Disease

Abstract: OBJECTIVE: To evaluate the long term effects of home mechanical ventilation (HMV) on pulmonary function, nighttime gas exchange, daytime arterial blood gases, sleep architecture and functional exercise capacity (6 min walk). Patients with respiratory failure attributable to thoracic restrictive disease (TRD) (kyphoscoliosis) or neuromuscular disease (NMD) were assessed, ventilated, trained and followed in a dedicated unit for the care of patients requiring long term ventilation.DESIGN: All patients admitted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The 6MWT is widely used and provides important prognostic information in several chronic cardiopulmonary disease states [13][14][15][16]. The primary outcome measurement of the 6MWT is the distance walked during a period of 6 min, which may include periods of rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6MWT is widely used and provides important prognostic information in several chronic cardiopulmonary disease states [13][14][15][16]. The primary outcome measurement of the 6MWT is the distance walked during a period of 6 min, which may include periods of rest.…”
Section: Discussionmentioning
confidence: 99%
“…A practical and simple measurement of functional status that is widely used as a clinical tool and outcome measure of patients with heart [13], obstructive lung disease [14], vascular [15], and neuromuscular disease [16] is the 6-min walk test (6MWT). However, the physiological abnormalities associated with disease severity and progression in IPF are not fully characterised by the distance of the 6MWT [7,9,12].…”
mentioning
confidence: 99%
“…10,12,13,19,20 Therefore, when identifying predictive risk factors, parameters observed after NIV initiation appear more valuable and reliable than those observed before the commencement of NIV. 18,20,22 We previously showed that P aCO 2 measured a few months after the start of long-term NIV is a possible prognostic factor in subjects with both restrictive thoracic disease 18 and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Arterial blood gases (ABGs) stabilize a few months after NIV initiation, and are sustained for many years in sub-jects with both COPD 10,18 and restrictive thoracic disease. 10,12,13,19,20 We previously showed that the average P aCO 2 of subjects breathing spontaneously decreases rapidly within several weeks of NIV, and thereafter increases gradually throughout long-term NIV. 18,20 We hypothesized that the adaptive mechanism that permits chronic hypercapnia occurs even in subjects receiving long-term NIV.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation